EFFECT OF PROFITABILITY, LEVERAGE, AND LIQUIDITY TO THE FIRM VALUE - Markonah, Markonah; Salim, Agus; Franciska, Johanna (Dinasti Publisher, 2020)
This study aims to determine the effect of profitability (ROA), leverage (DER) and liquidity (CR) on corporate value (PBV) in food and beverage manufacturing companies listed on the Jakarta Stock Exchange. Research Methodology research uses the data panel regression analysis method with the model used is fixed effect. The results of the F test show that profitability (ROA), leverage (DER), and liquidity (CR) adequately explain the influence on firm value (PBV). Result of research show that profitability (ROA) and leverage (DER) have significant effect to company value variable (PBV) while variable of liquidity (CR) has no significant effect to company value variable (PBV). The results of Determination Coefficient Test showed that the proportion influence of profitability, leverage and liquidity to company value was 86%. While the rest of 14% influenced by other variables.